2021
DOI: 10.1371/journal.pone.0256084
|View full text |Cite
|
Sign up to set email alerts
|

Rapport building and witness memory: Actions may ‘speak’ louder than words

Abstract: Building rapport during police interviews is argued as important for improving on the completeness and accuracy of information provided by witnesses and victims. However, little experimental research has clearly operationalised rapport and investigated the impact of rapport behaviours on episodic memory. Eighty adults watched a video of a mock crime event and 24-hours later were randomly allocated to an interview condition where verbal and/or behavioural (non-verbal) rapport techniques were manipulated. Memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 76 publications
4
14
0
Order By: Relevance
“…Rapport-building, also referred to as prosocial behaviour or supportive/attentive behaviour, is believed to be important for relieving some of the social demands of an interview (e.g., Kieckhaefer et al, 2014 ; Nahouli et al, 2021 ; Roberts et al, 2004 ; Webster et al, 2021 ), potentially increasing cognitive capacity for remembering (Dando et al, 2016 ; Fisher & Gieselman, 1992 ; Milne & Bull, 2016 ; Nahouil et al, 2021 ; Webster et al, 2021 ). Comfortable witnesses may well be better placed to devote finite cognitive resources to complex cognitions, here recalling episodic experiences (e.g., Fiske & Taylor, 2013 ; Frith & Frith, 2012 ; Gallese et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rapport-building, also referred to as prosocial behaviour or supportive/attentive behaviour, is believed to be important for relieving some of the social demands of an interview (e.g., Kieckhaefer et al, 2014 ; Nahouli et al, 2021 ; Roberts et al, 2004 ; Webster et al, 2021 ), potentially increasing cognitive capacity for remembering (Dando et al, 2016 ; Fisher & Gieselman, 1992 ; Milne & Bull, 2016 ; Nahouil et al, 2021 ; Webster et al, 2021 ). Comfortable witnesses may well be better placed to devote finite cognitive resources to complex cognitions, here recalling episodic experiences (e.g., Fiske & Taylor, 2013 ; Frith & Frith, 2012 ; Gallese et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite varying operationalisations of rapport-building, there is consensus that some rapport-building behaviour is better than none for positive outcomes (e.g., College of Policing, 2018 ; Gabbert et al, 2021 ; Ministry of Justice, 2022 ; Milne & Bull, 1999 ; Nahouli et al, 2021 ; Nash et al, 2014 ; Nash et al, 2016 ; Walsh & Bull, 2012 ), although experimental research findings are mixed. Some research indicates witnesses can provide more complete and accurate accounts when rapport-building behaviours are present (e.g., R. Collins et al, 2002 ; Holmberg & Madsen, 2014 ; Nahouli et al, 2021 ; Nash et al, 2016 ; Vallano & Shreiber Compo, 2011 ; Novotny et al, 2021 ), but this is not always the case (see Kieckhaefer et al, 2014 ; Sauerland et al, 2018 ). For example, verbal rapport-building (unaccompanied by appropriate behaviours) has been found to increase information yield (e.g., Novotny et al, 2021 ), whereas some have reported that verbal behaviour alone is less effective (e.g., Nahouli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations